2009
DOI: 10.1091/mbc.e08-09-0925
|View full text |Cite
|
Sign up to set email alerts
|

Fas Death Receptor Enhances Endocytic Membrane Traffic Converging into the Golgi Region

Abstract: The death receptor Fas/CD95 initiates apoptosis by engaging diverse cellular organelles including endosomes. The link between Fas signaling and membrane traffic has remained unclear, in part because it may differ in diverse cell types. After a systematic investigation of all known pathways of endocytosis, we have clarified that Fas activation opens clathrinindependent portals in mature T cells. These portals drive rapid internalization of surface proteins such as CD59 and depend upon actin-regulating Rho GTPas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
35
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 52 publications
2
35
0
Order By: Relevance
“…Our results suggested the reduction of Tumor Necrosis Factorrelated apoptosis-inducing ligand receptors 2 might be the reason Some investigators have reported that death receptors, such as Fas/CD95, undergo rapid internalization after triggering [Algeciras-Schimnich et al, 2002] and that Fas signaling enhances exocytosis after the initial wave of increased endocytosis [Reinehr and Haussinger, 2008]. Esposti also reported that the Fas enhances endocytic membrane traffic converging into the Golgi region [Degli Esposti et al, 2009]. Many recent studies have examined the role of Fas-mediated cell death in the vasculature, and Fas/FasL-mediated apoptosis has been proposed to play a role in physiological and pathological cell turnover in the vasculature [Fukuo et al, 1997;Sata and Walsh, 1998;Suhara et al, 1998].…”
Section: Discussionsupporting
confidence: 51%
“…Our results suggested the reduction of Tumor Necrosis Factorrelated apoptosis-inducing ligand receptors 2 might be the reason Some investigators have reported that death receptors, such as Fas/CD95, undergo rapid internalization after triggering [Algeciras-Schimnich et al, 2002] and that Fas signaling enhances exocytosis after the initial wave of increased endocytosis [Reinehr and Haussinger, 2008]. Esposti also reported that the Fas enhances endocytic membrane traffic converging into the Golgi region [Degli Esposti et al, 2009]. Many recent studies have examined the role of Fas-mediated cell death in the vasculature, and Fas/FasL-mediated apoptosis has been proposed to play a role in physiological and pathological cell turnover in the vasculature [Fukuo et al, 1997;Sata and Walsh, 1998;Suhara et al, 1998].…”
Section: Discussionsupporting
confidence: 51%
“…Interestingly, it had been reported that CD95 activation induces profound changes in intracellular membrane trafficking, dependent on caspase 8 activation, including also the secretory pathway (37). Our identification of a secretory/exocytic pathway of A-SMase activation offers a link between these events.…”
Section: Discussionsupporting
confidence: 50%
“…Given the rapid loss of free thiol content of Fas that is already apparent after 5 min, these events are induced rapidly and are unlikely to require internalization of Fas (12) or assembly of the DISC (Fig. 4C).…”
Section: Discussionmentioning
confidence: 99%